Dimensions on the Perception of Users Towards AI Generated Music - Pedrosa, Frederico; Figueiredo, Flávio; Machado, Alexei; Moriá, Ivan; Ferreira, Lucas (Anais do Simpósio Brasileiro de Computação Musical, 2025)
Music-generating Artificial Intelligence has reached a point where anyone, musician or not, can generate full-length songs from a simple textual query. As with other recent AI advances, such services are poised to impact various sectors of arts and industry, sparking social debate about their role in our daily lives. In this paper, we investigate the question: How do musicians and non-musicians perceive AI-Generated Music (AGM) services as a tool? We conducted a user-centered study (N=96) exploring perceptions of AGM in composition, production, education, and its ethical implications. The research is based on a quantitative survey analyzed using Exploratory Factor Analysis and Latent Profile Analysis, complemented by a thematic analysis of open-ended responses. Overall, results indicate a positive trend in opinions towards AGM for composition and production. The Latent Profile Analysis reveals two distinct participant groups. The larger group (77%) is highly enthusiastic about AGM for composition and production and also holds a more optimistic view of its ethical and cultural implications. The smaller group (23%) is broadly skeptical, holding a negative view of AGM’s compositional, production, and ethical aspects. Notably, both groups acknowledge the potential of AGM in education. This finding supports AGM as a promising tool for democratizing music composition and education.